Immunological Manifestations of Hepatitis E-Associated Acute and Chronic Liver Failure and Its Regulatory Mechanisms - Wu, Jian; Ling, Bai; Guo, Naizhou; Zhai, Guanghua; Li, Meifen; Guo, Yurong (Frontiers in Medicine, 2021)
Hepatitis E virus (HEV) is a common cause of viral hepatitis in developing countries, most commonly transmitted through the fecal-oral route. The virus is mainly of genotypes (GT) 1 and GT2 genotypes, and patients usually show symptoms of acute hepatitis. Due to the rising trend of HEV serological prevalence in global population, HEV has become an important public health problem in developed countries. Severe hepatitis caused by HEV includes acute and chronic liver failure (ACLF). ACLF frequently occurs in developed countries and is caused by overlapping chronic liver diseases of HEV with genotypes GT3 and GT4. Because the onset of hepatitis E is closely associated with immunity, it is critical to understand the immunological mechanism of hepatitis E associated with acute and chronic liver failure (HEV-ACLF). This review discusses the immunological manifestations and mechanisms of HEV-ACLF, intrahepatic immune microenvironment and treatment, and raises outstanding questions about the immunological mechanism and treatment of the disease.